Valores de referência da aldosterona e da razão aldosterona/renina para rastreio e diagnóstico de hiperaldosteronismo primário em pacientes com hipertensão arterial resistente - Silveira, João Vicente (2020)
Introduction: Primary hyperaldosteronism (PAH) is the main cause of endocrine hypertension in patients with secondary hypertension, and is a prevalent condition in resistant hypertensive patients. For PAH screening, the plasma aldosterone (A) concentration is simultaneously measured with the plasma renin activity (APR) or with the direct renin concentration (R), and the A/APR ratio values or A/R. According to the guidelines, the values that suggest the presence of PAH in the general population of hypertensive individuals are: aldosterone> 15ng/dL and A/APR≥30 ratio or A/R ratio ≥2.5. To confirm PAH, functional tests, adrenal imaging tests and, when available, catheterization of the adrenal veins for blood collection and hormonal measurements are performed. The reference values for suspected and diagnosed PH, based on the criteria presented, may vary in different populations. Few studies have evaluated the ratio A/APR and A/R for screening and confirmation of PAH in resistant hypertensive patients with comorbidities. Objectives: Determine the reference values of A, the ratio A/APR and A/R for suspected and diagnosed PH in patients with Resistant Arterial Hypertension (RAH), based on data from the electronic medical record of hypertensive patients treated at a tertiary service. Still, it is intended to determine if there are differences in the A/APR and A/R ratios in the male and female population. Methods: This is a retrospective analysis of a database of 6,000 patients of both sexes, treated between 2008 and 2018 in a specialized outpatient service. Data from all patients who had simultaneous A and APR or R measurements were included. Clinical (age, sex, systolic and diastolic blood pressure), anthropometric (weight, height, BMI) and laboratory (plasma and urinary sodium, potassium, urea, creatinine, glycemia and glycated hemoglobin) and were calculated at estimated glomerular filtration rates. Duplicate records and unpaired dosages of aldosterone and renin were excluded. Exploratory analyzes were carried out in order to establish the distribution of mean, median and percentile values (2.5 to 97.5%) of A, APR, R, and A/APR and A/R ratios in the general male population and feminine. The clinical and laboratory profile between genders was compared and patients whose ratio values were suspected of PAH were separated. Cutoff points were established using the ROC curve. New data were researched to verify if the PAH confirmatory exams were performed. A multivariate logistic regression model was derived and validated to predict the diagnosis of PAH. Results: The information of 3,268 patients was analyzed, with a mean age of 59.2 years with (SD = 13.3 years), a minimum age of 12 and a maximum age of 96 years. It was observed that 59.2% of the patients (N = 1,934) were female. It was found that the mean age, BMI, SBP, HbA1C and GFR were significantly higher in women compared to men, and an inverse pattern occurred with regard to urinary creatinine, urea and Na + values. The mean values of aldosterone, APR, A/APR and R were significantly higher in men compared to women. The A/R ratio showed no gender differences. A total of 349 patients (10.7% of the total) presented values of A and the A/APR ratio or A/R ratios compatible that indicated suspected PAH. Among these patients, 67 patients underwent confirmatory evaluation, and PAH was confirmed by the presence of adrenal adenoma. Through the analysis of multivariate logistic regression, the ROC curve was obtained for the variables of interest. In our population, it was found that the cutoff point with aldosterone≥13.35 ng/dL and the A/APR values ≥ 26.88 or A/R ≥ 2.45 respectively had an adjusted odds ratio of 15 and 75 times greater than presenting PAH in relation to patients without this condition. Conclusion: Our data demonstrate that new reference points for aldosterone, the ratio A/APR and A/R can be a convenient option for the measurement and screening of the diagnosis of PAH in a population of resistant hypertensive patients.